Protective effects of erdosteine, vitamin E, and vitamin C on renal injury induced by the ischemia-reperfusion of the hind limbs in rats - Sirmali, Rana; Armagan, Abdullah; Oktem, Faruk; Uz, Efkan; Kirbas, Aynur; DÖNMEZ, SONER; Yilmaz, Haci Ramazan; Silay, Mesrur Selcuk; Sirmali, Mehmet (My University, 2015)
Background/aim: To compare the protective efficacy of erdosteine and vitamins C and E against renal injury caused by hind limb ischemia-reperfusion (I/R).